The light‐dark cycle controls peripheral rhythmicity in mice with a genetically ablated suprachiasmatic nucleus clock. Issue 11 (25th July 2014) - Husse, Jana; Leliavski, Alexei; Tsang, Anthony H.; Oster, Henrik; Eichele, Gregor
Abstract : The mammalian circadian timing system consists of a master pacemaker in the suprachiasmatic nucleus (SCN), which is thought to synchronize peripheral clocks in various organs with each other and with external time. Our knowledge about the role of the SCN clock is based mainly on SCN lesion and transplantation studies. We have now directly deleted the SCN clock using the Cre/LoxP system and investigated how this affects synchronization of peripheral rhythms. Impaired locomotor activity and arrhythmic clock gene expression in the SCN confirm that the SCN clockwork was efficiently abolished in our mouse model. Nonetheless, under light‐dark (LD) conditions, peripheral clocks remained rhythmic and synchronized to the LD cycle, and phase relationships between peripheral clocks were sustained. Adaptation to a shifted LD cycle was accelerated in SCN clock‐deficient mice. Moreover, under zeitgeber‐free conditions, rhythmicity of the peripheral clock gene expression was initially dampened, and after several days peripheral clocks were desynchronized. These findings suggest that the SCN clock is dispensable for the synchronization of peripheral clocks to the LD cycle. A model describing an SCN clock‐independent pathway that synchronizes peripheral clocks with the LD cycle is discussed.—Husse, J., Leliavski, A., Tsang, A. H., Oster, H., Eichele, G., The light‐dark cycle controls peripheral rhythmicity in mice with a genetically ablated suprachiasmatic nucleus clock. FASEB J. 28, 4950–4960 (2014). www.fasebj.org